Evaluation of a new molecular typing strategy of Pseudomonas aeruginosa - Magalhães, Bárbara Gomes (2015)
Pseudomonas aeruginosa is the third leading cause of hospital acquired infection in intensive care unit (ICU) patients. This microorganism holds responsibility in a high number of nosocomial infections and their severity. Because it is ubiquitous in the environment and also constitutes the endogenous microbiota of hospitalized patients, there is a need to use powerful molecular typing methods to establish clonal relationships between individual isolates. Double Locus Sequence Typing (DLST) has recently been used in the analysis of P. aeruginosa strains relatedness, proving to be efficient, easy, and also reducing the working time and costs of analysis. Another typing technique called Double Digest Sequence Label (DDSL) had also been reported in the molecular study of this microorganism. A higher discriminatory power makes DDSL a putative typing complement to resolve DLST clusters in specific situations. From 2010 to 2012, an increase in P. aeruginosa infections incidence was observed in the ICUs of the Lausanne University Hospital, Switzerland. During this period, 689 isolates were retrieved from 254 patients. All isolates were analyzed with DLST and grouped in 46 DLST clusters, from which 4 clusters were further investigated in this study (cluster 1_18, 1_21, 6_7 and 28_77). These 4 clusters were retrospectively typed with the DDSL method to verify if an improved discrimination of isolates could be achieved. To do so, a first DDSL optimization step was performed, which resulted in good quality fingerprinting profiles. However, a quantitative analysis of the results using BioNumerics software was not possible. Visual comparison of DDSL fingerprinting patterns within each cluster allowed the formation of different DDSL types, but not the determination of bands differences between them. Epidemiological data showed that contamination of humid environments probably played an important role in the dissemination of P. aeruginosa strains in this outbreak. Comparison of epidemiological and molecular information showed that most of undistinguishable DDSL types were epidemiologically linked, leading to the assumption that patient-to-patient transmission should be highly suspected, as seen for cluster 1_18. Nevertheless, strain evolution should be considered when studying a long period outbreak. In conclusion, this new typing strategy of P. aeruginosa allowed the acquisition of a general picture about this outbreak’s epidemiology. Nevertheless, the DDSL is a technically complex, time consuming and subjective technique, not efficient to be use for epidemiological investigation purposes.